Flow Properties of Spices Measured with Powder Flow Tester and Ring Shear Tester-XS - Slettengren, Katarina; Xanthakis, Epameinondas; Ahrne, Lilia; Windhab, Erich J. (My University, 2016)
Due to the importance of powder flow properties and the variety of available measuring methods, several studies were published regarding the comparison of different flow properties testers. Within this work, a ring shear tester from Dr. Dietmar Schulze and a powder flow tester from Brookfield Engineering Laboratories Inc. were compared for cumin (Cuminum cyminum L.), oregano (Origanum vulgare), and onion (Allium cepa) powder and granules. The spices showed similar flow behavior from both methods. Flow function plots and effective angle of internal friction measurements indicated contiguous trends and showed that the methods were comparable.
Keywords: Powders; Flow properties; Ring shear testers; RST; PFT